An active vocabulary learning tool for primary school students with a hearing impairment - Santichai Wicha (2018)
This paper illustrates a new way for teaching Thai primary school students with a hearing impairment in order to improve their English vocabulary learning abilities. A supplementary educational technology tool, known as the 'total communication with animation dictionary' (TCAD) has been proposed in this study. Since the TCAD had already been implemented in the experimental group we found that the tool supported vocabulary long-term memory retention. With the study extended to the set of population and number of vocabularies increased to these students. The results confirmed that the TCAD is an active supplementary vocabulary learning and a comprehensive instruction tool for the hearing impaired. © 2011 Inderscience Enterprises Ltd.